Action spectroscopy of chlorophyll and other coordination complexes. (August 2015) - Stockett, Mark H; Houmøller, Jørgen; Kjær, Christina; Milne, Bruce F; Musbat, Lihi; Rubio, Angel; Toker, Yoni; Nielsen, Steen Brøndsted
Synopsis: Action spectroscopy provides key insights into the nature of electronic transitions of coordination complexes such as porhyrin-containing biochromophores like chlorophyll or transition metal complexes such as tris(bipyridine)ruthenium.